The effect of depressive symptoms on disability-free survival in healthy older adults: A prospective cohort study - Roebuck, G.; Lotfaliany, M.; Agustini, B.; Forbes, M.; Mohebbi, M.; McNeil, J.; Woods, R.L.; Reid, Christopher; Nelson, M.R.; Shah, R.C.; Ryan, J.; Newman, A.B.; et al. (WILEY, 2023)
Background: Gerontology and ageing research are increasingly focussing on healthy life span (healthspan), the period of life lived free of serious disease and disability. Late-life depression (LLD) is believed to impact adversely on physical health. However, no studies have examined its effect on healthspan. This study investigated the effect of LLD and subthreshold depression on disability-free survival, a widely accepted measure of healthspan. Methods: This prospective cohort study used data from the ASPirin in Reducing Events in the Elderly study. Participants were aged ≥70 years (or ≥65 years for African-American and Hispanic participants) and free of dementia, physical disability and cardiovascular disease. Depressive symptoms were measured using the 10-item Centre for Epidemiological Studies Depression Scale (CES-D-10). LLD and subthreshold depression were defined as CES-D-10 scores ≥8 and 3–7, respectively. Disability-free survival was defined as survival free of dementia and persistent physical disability. Results: A total of 19,110 participants were followed up for a maximum of 7.3 years. In female participants, LLD was associated with lower disability-free survival adjusting for sociodemographic and lifestyle factors, medical comorbidities, polypharmacy, physical function and antidepressant use (HR, 1.50; 95% CI, 1.23–1.82). In male participants, LLD was associated with lower disability-free survival adjusting for sociodemographic and lifestyle factors (HR, 1.30; 95% CI, 1.03–1.64). Subthreshold depression was also associated with lower disability-free survival in both sexes. Conclusions: LLD may be a common and important risk factor for shortened healthspan.